Climate change and the past, present, and future of biotic interactions - Blois Jessica L et al. (Science, 2013)
Biotic interactions drive key ecological and evolutionary processes and mediate ecosystem responses to climate change. The direction,frequency,and intensity of biotic interactions can in turn be altered by climate change. Understanding the complex interplay between climate and biotic interactions is thus essential for fully anticipating how ecosystems will respond to the fast rates of current warming, which are unprecedented since of the last glacial period. We highlight episodes of climate change that have disrupted ecosystems and trophic interactions over time scales ranging from years to millennia by changing species relative abundances and geographic ranges, causing extinctions, and creating transient and novel communities dominated by generalist species and interactions. these patterns emerge repeatedly across disparate temporal and spatial scales, suggesting the possibility of similar underlying processes. Based on these findings, we identify knowlwdge gaps and fruitful areas for research that will further our understanding of the effects of climate change on ecosystems.
Keywords: Climate change; Mass extinctions